Efecto de las micorrizas arbusculares sobre la fase inicial de crecimiento de plantas de Humulus lupulus l. - Sagadin, Monica Beatriz; Galli, Maria Carolina; Risso, Ariel; Ruiz Díaz, Zulma Noemí; Ramaciotti, Julieta Fernanda; Denegri, Andrea; Ocaño, Sonia (Asociación Argentina de Horticultura (ASAHo), 2024)
Poster